Comparison of Maintenance Cost, Labor Demands, and System Performance for LID and Conventional Stormwater Management - Houle, James J; Roseen, Robert M; Ballestero, Thomas P; Puls, Timothy A; Sherrard, James (Journal of environmental engineering (New York, N.Y.), 2013)
AbstractThe perception of the maintenance demands of low impact development (LID) systems represents a significant barrier to the acceptance of LID technologies. Despite the increasing use of LID over the past two decades, stormwater managers still have minimal documentation in regard to the frequency, intensity, and costs associated with LID operations and maintenance. Due to increasing requirements for more effective treatment of runoff and the proliferation of total maximum daily load (TMDL) requirements, there is a greater need for more documented maintenance information for planning and implementation of stormwater control measures (SCMs). This study examined seven different types of SCMs for the first 2–4 years of operations and studied maintenance demands in the context of personnel hours, costs, and system pollutant removal. The systems were located at a field facility designed to distribute stormwater in parallel in order to normalize watershed characteristics including pollutant loading, sizing, and rainfall. System maintenance demand was tracked for each system and included materials, labor, activities, maintenance type, and complexity. Annualized maintenance costs ranged from $2,280/ha/year for a vegetated swale to $7,830/ha/year for a wet pond. In terms of mass pollutant load reductions, marginal maintenance costs ranged from $4–$8/kg/year TSS removed for porous asphalt, a vegetated swale, bioretention, and a subsurface gravel wetland, to $11–$21/kg/year TSS removed for a wet pond, a dry pond, and a sand filter system. When nutrients such as nitrogen and phosphorus were considered, maintenance costs per gper year removed ranged from reasonable to cost-prohibitive, especially for systems with minimal to no nutrient removal. As such, SCMs designed for targeting these pollutants should be selected carefully. The results of this study indicate that generally, LID systems, as compared to conventional systems, have lower marginal maintenance burdens (as measured by cost and personnel hours) and higher water quality treatment capabilities as a function of pollutant removal performance. Cumulative amortized system maintenance expenditures equal the SCM capital construction costs (in constant dollars) in 5.2 years for wet ponds and in 24.6 years for the porous asphalt system. In general, SCMs with higher percentages of periodic and predictive or proactive maintenance activities have lower maintenance burdens than SCMs with incidences of reactive maintenance.